From Tear to Fear: Posttraumatic Stress Disorder in Patients With Acute Type A Aortic Dissection. Issue 9 (5th May 2020) - Pasadyn, Selena R.; Roselli, Eric E.; Artis, Amanda S.; Pasadyn, Cassandra L.; Phelan, Dermot; Hurley, Karen; Desai, Milind Y.; Blackstone, Eugene H.
Abstract : Background: Acute type A aortic dissection presents with abrupt onset of pain that requires emergency surgery. However, minimal research exists on posttraumatic stress disorder (PTSD) in survivors. We aimed to quantify the prevalence and describe characteristics of PTSD in patients following dissection. Methods and Results: A total of 295 adult survivors of surgical dissection with an email on file were administered a cross‐sectional online survey about their dissection experience; 137 returned questionnaires, and 129 (94%) responded to the 4‐item Primary Care PTSD portion of the survey that was part of a larger lifestyle survey designed to study survivors of aortic dissection and surgery. In addition to the PTSD screening, it inquired about current sexual activity, exercise habits, and employment within the preceding 30 days. At a median of 6.8 years (quartile 1=2.6, quartile 3=8.9 years) after dissection, 23% of patients (30/129) screened positive for PTSD, with 44% (57/129) stating that within the past month they felt constantly on guard or watchful or were easily startled. Of those who screened positive and matched to their electronic medical record (n=27), only 2 (7.4%) had been tested and clinically diagnosed with PTSD. Patients who screened positive for PTSD were more likely to report limited current sexual activity than those who did not (odds ratio, 5.3; 95% CI, 1.9–15 [ P= 0.0006]). Conclusions: PTSD is an important mental health consideration in aortic dissection survivors. Physicians should screen these patients for PTSD at follow‐up visits to identify those who test positive and refer them for further testing and treatment, such as trauma‐focused psychotherapy or medication.